Peninsular Malaysia’s Negrito orang Asli and its theory of African origin - Endom Ismail; Farahnaz Amini; Shairah Abdul Razak; Husna Mohd Zaini; Reza Farhour; Bin Alwi Zilfalil (Universiti Kebangsaan Malaysia, 2013)
Negritos of Peninsular Malaysia have physical features which strongly resemble the African pygmies rather than any of the other main South East Asian ethnic groups. In addition, their features are also completely different from the two other large sub-groups of the Peninsular Malaysia Orang Asli, i.e. Senoi and Proto-Malay. In this study, we genetically screened three African-specific markers, Glucose-6 Phosphate Dehydrogenase (G6PD) gene PvuII Type 2 polymorphism and A- mutation; and Sickle Cell trait in 103 unrelated individuals with G6PD deficiency. None of the Negritos’ samples carried A- and Sickle cell mutations but all males and females have the PvuII Type 2 polymorphism. The same results were seen in all DNA samples of the Malaysian’s Malay, Chinese and Indians. Additionally, all females in this study were homozygous for PvuII Type 2 polymorphism. Thus, we concluded that this polymorphism is widespread in all Malaysian population and is not unique to just Africans. However, these findings indicated that the polymorphism was widely conserved and can be used to study the African descendant in any world population hitherto supporting the ‘Out of Africa’ theory.